A novel ductile machining model of single-crystal silicon for freeform surfaces with large azimuthal height variation by ultra-precision fly cutting. (December 2018) - Sun, Zhanwen; To, Suet; Zhang, Shaojian
Abstract: Ultra-precision fly cutting (UPFC) is an important technology in the fabrication of freeform surfaces on single-crystal silicon. However, the insufficient understanding of the ductile machining mechanisms in UPFC of silicon under a large depth of cut highly limits the practical fabrication of freeform surfaces with large azimuthal height variation (AHV). Especially, no work has been found on studying the ductile machining model in UPFC of silicon considering both feed and step motion of the diamond tool. In this study, a novel ductile machining model in UPFC of silicon is proposed to demonstrate the superiority of UPFC on achieving the deep ductile-cut region. Experimental validation has been conducted by fabricating two kinds of freeform surfaces, namely micro-grooves and an F-theta lens, on silicon. This paper theoretically and experimentally elaborates that the chip thickness of UPFC is not only determined by the machining parameters, but also is the inversely proportional function of the swing distance of the diamond tool. Thus, by employing a large enough swing distance, much thinner chips can be generated by UPFC even when machining under large cutting depths and feed rates. Therefore, a deep ductile-cut region of silicon can be achieved by UPFC with a large swing distance. Freeform surfaces with tens of micrometers of AHV can be successfully fabricated on silicon by UPFC without the generation of brittle fractures. Graphical abstract: Highlights: A novel ductile machining model based on ultra-precison fly cutting is proposed. Freeform surfaces with large azimuthal height variation are machined on singel-crystal silicon. Much deeper ductile region is observed by the model when comared with plunge cutting. Cutting mechanism is analyzed by chip morphology and material phase transformation.